Low protein diets in patients with chronic kidney disease: a bridge between mainstream and complementary-alternative medicines?. Issue 1 (December 2016) - Piccoli, Giorgina; Capizzi, Irene; Vigotti, Federica; Leone, Filomena; D'Alessandro, Claudia; Giuffrida, Domenica; Nazha, Marta; Roggero, Simona; Colombi, Nicoletta; Mauro, Giuseppe; Castelluccia, Natascia; Cupisti, Adamasco; et al.
Abstract Dietary therapy represents an important tool in the management of chronic kidney disease (CKD), mainly through a balanced reduction of protein intake aimed at giving the remnant nephrons in damaged kidneys a "functional rest". While dialysis, transplantation, and pharmacological therapies are usually seen as "high tech" medicine, non pharmacological interventions, including diets, are frequently considered lifestyle-complementary treatments. Diet is one of the oldest CKD treatments, and it is usually considered a part of "mainstream" management. In this narrative review we discuss how the lessons of complementary alternative medicines (CAMs) can be useful for the implementation and study of low-protein diets in CKD. While high tech medicine is mainly prescriptive, prescribing a "good" life-style change is usually not enough and comprehensive counselling is required; the empathic educational approach, on which CAMs are mainly, though not exclusively based, may support a successful personalized nutritional intervention. There is no gold-standard, low-protein diet for all CKD patients: from among a relatively vast choice, the best compliance is probably obtained by personalization. This approach interferes with the traditional RCT-based analyses which are grounded upon an assumption of equal preference of treatments (ideally blinded). Whole system approaches and narrative medicine, that are widely used in the study of CAMs, may offer ways to integrate EBM and personalised medicine in the search for innovative solutions respecting individualization, but gaining sound data, such as with partially-randomised patient preference trials.